Dark Rover Ant: Brachymyrmex patagonicus Mayr - David Tamayo (EDIS)
The dark rover ant is a tiny ant, native to Argentina and Paraguay, that was introduced relatively recently to the United States. It is established in the Gulf states and in some urban areas of Arizona and Nevada. It is a nuisance species because it invades and establishes nests in structures. This 6-page fact sheet was written by David Tamayo and published by the UF Department of Entomology and Nematology, August 2011.